How Digital Finance Affects the Continuous Technological Innovation of Chinese Energy Companies? - Guo, Zhongkun; Peng, Yulian; Chen, Yajing (Frontiers in Energy Research, 2022)
This paper discusses the impact of digital finance development on the continuous technological innovation and its mechanism in China’s energy companies. Analyzing the data of A-share listed energy companies in China's Shanghai and Shenzhen stock markets from 2011–2018, using a fixed effects model, we find that digital finance development played a positive role in stimulating continuous technological innovation in Chinese energy companies. Moreover, we find that risk-taking plays a mediating effect, which is the development of digital finance encourages Chinese energy companies to carry out continuously innovative activities by increasing the level of corporate risk-taking. Finally, we find that in non-state-owned, small and highly externally funded energy companies, digital finance development shows a stronger effect in driving continuous technological innovation in Chinese energy companies through risk-taking. Our results highlight the role of risk-taking as an important mediator in the relationship between digital finance development and continuous technological innovation. It has enlightenment for China to make better use of digital finance to empower energy companies to continue to innovate.